Ballistic impacts on an anatomically correct synthetic skull with a surrogate skin/soft tissue layer - Mahoney, Peter F.; Carr, Debra J.; Arm, Richard; Gibb, Iain; Hunt, Nicholas; Delaney, Russ J. (Springer, 2017)
The aim of this work was to further develop a synthetic model of ballistic head injury by the addition of skin and soft tissue layers to an anatomically correct polyurethane skull filled with gelatine 10% by mass. Six head models were impacted with 7.62 x 39 mm full metal jacket mild steel core (FMJ MSC) bullets with a mean velocity of 652 m/s. The impact events were filmed with high-speed cameras. The models were imaged pre- and post-impact using computed tomography. The models were assessed post impact by two experienced Home Office pathologists and the images assessed by an experienced military radiologist. The findings were scored against real injuries. The entry wounds, exit wounds and fracture patterns were scored positively, but the synthetic skin and soft tissue layer was felt to be too extendable. Further work is ongoing to address this.
Keywords: Head injury; CT scanning; Ballistic images; Synthetic skin